2019
DOI: 10.1016/j.apcatb.2019.117950
|View full text |Cite
|
Sign up to set email alerts
|

Co-electrolysis of H2O and CO2 on exsolved Ni nanoparticles for efficient syngas generation at controllable H2/CO ratios

Abstract: Syngas (CO+H2) is a key-intermediate for the production of liquid fuels via the Fischer-Tropsch process. An emerging technology for generating syngas is the co-electrolysis of H2O/CO2 in solid oxide cells powered by renewable electricity. An application of this technology, however, is still challenging because the Ni-based cermet fuel electrodes are susceptible to degradation under redox and coking conditions, requiring protective hydrogen atmosphere to maintain stable operation. Perovskite oxides are the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 47 publications
4
67
0
Order By: Relevance
“…Ni or Fe) is incorporated into the crystal lattice of the perovskite backbone under oxidizing conditions and is released (exsolved) on the surface as metal nanoparticles, either by exposure to a reducing atmosphere or by applying a large cathodic overpotential. 17,18 It is generally admitted that exsolution is favoured upon A-site deciency: when the oxygen vacancy concentration is high enough to partially destabilize the perovskite lattice due to the high deciency on A-and O-sites, metal particles from the B-site exsolve while charge balance of the lattice is maintained. 19 A recent study by Neagu et al about Ni exsolution on lanthanum-calcium doped titanates and lanthanum-cerium doped titanates by in situ observation with environmental transmission microscopy (ETEM) showed that the exsolution phenomena and thus the shape of the resulting nanoparticles are signicantly affected by the temperature and the oxygen partial pressure (pO 2 ), 20 being important operating parameters for the rSOC reactors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni or Fe) is incorporated into the crystal lattice of the perovskite backbone under oxidizing conditions and is released (exsolved) on the surface as metal nanoparticles, either by exposure to a reducing atmosphere or by applying a large cathodic overpotential. 17,18 It is generally admitted that exsolution is favoured upon A-site deciency: when the oxygen vacancy concentration is high enough to partially destabilize the perovskite lattice due to the high deciency on A-and O-sites, metal particles from the B-site exsolve while charge balance of the lattice is maintained. 19 A recent study by Neagu et al about Ni exsolution on lanthanum-calcium doped titanates and lanthanum-cerium doped titanates by in situ observation with environmental transmission microscopy (ETEM) showed that the exsolution phenomena and thus the shape of the resulting nanoparticles are signicantly affected by the temperature and the oxygen partial pressure (pO 2 ), 20 being important operating parameters for the rSOC reactors.…”
Section: Introductionmentioning
confidence: 99%
“…(La,Sr)(Cr,M)O 3 perovskites (M ¼ Mn, Fe, Co and Ni) have been recently investigated for H 2 O electrolysis, CO 2 electrolysis and H 2 O-CO 2 co-electrolysis: mostly in stoichiometric formulations 21 and a few with A-site deciency. 17,22 However, the Ni exsolution phenomena on lanthanum chromites upon temperature and atmosphere variation remain unclear, and the performance of such perovskite electrodes still needs to be improved in order to achieve comparable results with the typical Ni-cermet fuel electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[78] Coelectrolysis of H 2 O and CO 2 cells have also been demonstrated to employ exsolved Ni nanoparticles for efficient syngas generation exhibiting up to 20% improved electrocatalytic syngas production rates when compared to the commonly used Ni-YSZ while stable operation was achieved without the need for protective H 2 atmosphere. [94] Ni exsolution is also widely used in catalytic applications such as the transformation of hydrocarbons into valuable products especially in areas such as methane reformation or production. [95][96][97][98][99] This is not surprising since Ni-containing catalysts are often considered to be state of the art for the reformation of a range of hydrocarbons (Figure 15b).…”
Section: Nickelmentioning
confidence: 99%
“…[1,2] To date, the photochemical production of syngas with flexible and controllable stoichiometric ratios has been a challenge. Electrocatalytic syngas synthesis has been shown, [3][4][5] however there remain few examples of photocatalytic generation of syngas from the reduction of CO 2 and H + in one pot. [6,7] This may be attributed to the fact that proton reduction is significantly more thermodynamically favorable and that selective CO 2 reduction to CO is more challenging.…”
Section: Introductionmentioning
confidence: 99%